Conceptualising Violence Through a Gender Lens: Regulation and Strategies for Prevention and Redress - Lippel, Katherine (Université d'Ottawa | University of Ottawa, 2018)
Violence against women is notoriously pervasive and has been studied at length. Surprisingly less is known about the different facets of violence to which women are exposed at work. This article presents findings from a working paper commissioned by the Gender, Equality and Diversity Branch of the International Labour Organization to provide an overview of literature on occupational violence, from a broad range of disciplinary perspectives, including both conceptual papers and descriptions of regulatory frameworks from around the world. It first looks at definitions of workplace violence, including physical, psychological, sexual and discriminatory violence, including harassment, as well as workplace related intimate partner violence. It then turns to determinants of occupational violence, including psychosocial risk factors and structural violence. A discussion of the importance of using a gender lens to understand occupational violence and its roots concludes the conceptual section. Finally, the article presents different regulatory approaches to the prevention of occupational violence including both international and national instruments, again examined through a gender lens. It presents the case, in conclusion, for an integrated regulation of violence at work in * University of Ottawa, klippel@uottawa.ca. Violence against women is notoriously pervasive and has been studied at length. Surprisingly less is known about the different facets of violence to which women are exposed at work. This article presents findings from a working paper commissioned by the Gender, Equality and Diversity Branch of the International Labour Organization to provide an overview of literature on occupational violence, from a broad range of disciplinary perspectives, including both conceptual papers and descriptions of regulatory frameworks from around the world. It first looks at definitions of workplace violence, including physical, psychological, sexual and discriminatory violence, including harassment, as well as workplace related intimate partner violence. It then turns to determinants of occupational violence, including psychosocial risk factors and structural violence. A discussion of the importance of using a gender lens to understand occupational violence and its roots concludes the conceptual section. Finally, the article presents different regulatory approaches to the prevention of occupational violence including both international and national instruments, again examined through a gender lens. It presents the case, in conclusion, for an integrated regulation of violence at work in order to maximize uptake of rights and effectiveness of prevention measures while promoting violence free workplaces for men and women.
Keywords: Occupational Violence; Work; Gender; Regulation; Prevention